THE IMPACT OF WORK ENVIRONMENT AND LEADERSHIP ON THE PERFORMANCE OF GENERATION Z EMPLOYEES - Octakistis, Renata; Zakariya Al Anshori; Dewi Prastiwi (Economic and Bussiness Faculty, Dr Soetomo University, 2024)
The aim of this study is to determine whether the performance of Generation Z employees in Surabaya is influenced by their work environment and leadership. The subjects selected for this research were Generation Z individuals aged 17 to 29 in Surabaya. The study sampled 150 Generation Z workers from the city. A quantitative approach was employed, utilizing multiple linear regression analysis. The findings indicate that both the work environment and leadership positively impact the performance of Generation Z employees in Surabaya. This research was limited to the population of Surabaya. Given this limitation, future studies are recommended to broaden the sample area and include additional variables to enhance the effectiveness of the results.